The Radical Anion, Dianion and Electron Transport Properties of Tetraiodotetraazapentacene. Issue 69 (25th October 2022) - Wiesner, Thomas; Wu, Zhu; Han, Jie; Ji, Lei; Friedrich, Alexandra; Krummenacher, Ivo; Moos, Michael; Lambert, Christoph; Braunschweig, Holger; Rudin, Benjamin; Reiss, Hilmar; Tverskoy, Olena; et al.
Abstract: Tetraiodotetraazapentacene I4 TAP, the last missing derivative in the series of halogenated silylated tetraazapentacenes, was synthesized via condensation chemistry from a TIPS‐ethynylated diaminobenzothiadiazol in three steps. Single and double reduction furnished its air‐stable monoanion and relatively air‐stable dianion, both of which were characterized by crystallography. All three species are structurally and spectroscopically compared to non‐halogenated TAP and Br4 TAP . I4 TAP is an n‐channel material in thin‐film transistors with average electron mobilities exceeding 1 cm 2 (Vs) −1 . Abstract : Filling the gap in the series of halogenated azaacenes. Tetraiodotetraazapentacene I4 TAP is prepared and characterized. Its stable radical anion and high mobilities in organic field‐effect transistors make I4 TAP a formidable n‐type semiconductor.